A Protein‐Nanocellulose Paper for Sensing Copper Ions at the Nano‐ to Micromolar Level. (7th December 2016) - Weishaupt, Ramon; Siqueira, Gilberto; Schubert, Mark; Kämpf, Michael M.; Zimmermann, Tanja; Maniura‐Weber, Katharina; Faccio, Greta
Abstract : Tracing heavy metals is a crucial issue in both environmental and medical samples. In this work, a sensing biomolecule, the cyanobacterial C‐phycocyanin (CPC), is integrated into a nanocellulose matrix, and with this, a biosensor for copper ions is developed. The assembly of CPC‐functionalized nanocellulose into a red‐fluorescent, copper‐sensitive hybrid film "CySense", enhances protein stability and facilitates the reuse and the regeneration of the sensor for several cycles over 7 days. CySense is suitable for the analysis of complex medical samples such as human serum filtrate. The reported biosensor reliably detects copper ion contents with a lower detection limit of 200 × 10 −9 m and an IC50 of 4.9 × 10 −6 m as changes in fluorescence emission intensity that can be measured with a fluorimeter or a microarray laser scanner. Abstract : A biosensor for the detection of copper ions in complex samples by fluorescence measurement is made possible by the immobilization of the sensing protein C‐phycocyanin into a nanocellulose‐based film. With an optimized immobilization strategy, the fabrication of CySense films improves the thermal stability of the sensing protein and enables reuse.